ENGAGING COMPUTER ASSISTED LANGUAGE LEARNING (CALL) IN 2013 NATIONAL EDUCATION CURRICULUM - Endah Januarti (Universitas PGRI Madiun, 2015)
The implementation of CALL in the classroom to improve the students’ reading capability is successful viewed from some dimensions. The implementation of CALL in the classroom can change the role of students and teacher in classroom interaction; from teacher-centered to students-centered which makes the students be the central of the instructional process. CALL also improves the process of learning. It motivates the students to learn, provides various teaching materials, and triggers the students’ creativity by providing nearly unlimited learning materials. However, in integrating the application into the curriculum the teacher need to make the application meaningful for the students. For this, the function of the computer is to support the learning objectives. The implementation of CALL in the classroom is very essential in enhancing the students’ capability in English language learning. Therefore, it is recommended that; (1) English teachers should pave the way the development of technology to improve their quality of teaching; (2) English teacher need to be creative and innovative in developing learning strategies to create better learning environments; (3) Schools have to provide the students better facilities; and (4) Due to the limited time to study at school, it is recommended for the students to study after class since CALL provides them opportunities to develop themselves to improve their language competence, especially reading.